1988
DOI: 10.1029/gl015i001p00017
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of sticking coefficients and heterogeneous reactions important in the Antarctic stratosphere

Abstract: Laboratory studies of sticking coefficients of H2O, HCl, Cl2 and HNO3 on ice and heterogeneous reactions of ClONO2 with ice or HCl/ice have been performed in a fast flow reactor. A quadrupole mass spectrometer with electron impact ionization was used as a detector. Measured sticking coefficients are: 0.3 (+0.7. −0.1) for H2O, 0.4 (+0.6, −0.2) for HCl, <1.0 × 10−4 for Cl2, and 0.3 (+0.7, −0.1) for HNO3 at 200 K. The reaction probability of ClONO2 on ice was found to be 0.06 (±0.03) while HOCl was observed as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
161
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(169 citation statements)
references
References 15 publications
8
161
0
Order By: Relevance
“…Despite the use of larger HCl mole fractions, the uptake coefficients quoted by are significantly lower than the values of Leu et al Both Leu et al (1988) and detected ClNO 2 as product, but did not quantify the yield. found that small amounts of HCl increased the N 2 O 5 uptake coefficient slightly, the results in qualitative agreement with those of Leu (1988). At high concentrations of HCl (which induced surface melting) the uptake coefficient increased as did the yield of ClNO 2 .…”
Section: Preferred Valuessupporting
confidence: 78%
See 3 more Smart Citations
“…Despite the use of larger HCl mole fractions, the uptake coefficients quoted by are significantly lower than the values of Leu et al Both Leu et al (1988) and detected ClNO 2 as product, but did not quantify the yield. found that small amounts of HCl increased the N 2 O 5 uptake coefficient slightly, the results in qualitative agreement with those of Leu (1988). At high concentrations of HCl (which induced surface melting) the uptake coefficient increased as did the yield of ClNO 2 .…”
Section: Preferred Valuessupporting
confidence: 78%
“…There is substantial disagreement between the Kenner et al (1993) and studies on one hand, and the Leu (1988) and studies on the other hand. One of the reasons could simply lie in the ice preparation method leading to highly porous films in case of vapour deposition from the gas phase.…”
Section: Comments On Preferred Valuesmentioning
confidence: 78%
See 2 more Smart Citations
“…We note that this value is very different from what would be expected if surface processes only were operative, and mass accommodation coefficients α could be used to predict X kin . The parameter α HCl has been measured in the laboratory around −80 • C, and values between 0.1 and 1 have been found (Leu et al, 1988;Hanson and Ravishankara, 1992). Similarly, α H 2 O is in the range 0.1 to 1 (Haynes et al, 1992 and references therein), so that α HCl /α H 2 O is expected to be in the range 0.1 to 10.…”
Section: Resultsmentioning
confidence: 99%